The Effect Of The Hybrid Additions on the Bending and Tensile Behavior for the Hybrid Composite Material Reinforced by Short Fibers and the Zeolite Particles by Multifarious Grain Size - Sallal, Hayder Abbas (Al-Nahrain Journal for Engineering Sciences, 2017)
Consider polymers and polymer matrix composite are the basis of the most prevalent material in all industrial and medical fields because of its properties qualify to occupy an advanced position among other engineering materials because of its good properties._x000D_ Therefore, This work focuses on the preparation of base polymer matrix composite materials and study non-saturated polyester as matrix has been strengthened by zeolite particles different grain sizes (25 - 65 - 75) µm and different volume fractions (1,5 - 3 - 4,5 - 6 - 7,5 - 10) % was strengthened by Carbon short fibers and constant volume fraction (8%),the tests tensile and bending according to ASTM specifications, respectively. Through the results it was observed that the maximum tensile strength improved through hybrid reinforcement when reached the maximum value when the grain size (25 µm ) and at volume fraction (7.5%), reaching ( 94 N/mm2 )compared with the rest of sizes and at the same volume fraction reaching (78 N/mm2 for 65 µm , 69 N/mm2 for 75 µm), As for the bending test has been getting maximum Flexural resistance at grain size (25 µm) at volume fraction ( 6%) reached to(111 N/mm2) ,if compared with the rest of sizes at the same volume fraction reaching (100 N/mm2 for 65 µm,79 N/mm2 for 75 µm) while was obtained on the maximum bending modulus at grain size (25 µm) and at volume fraction (10%) reach to (8099 N/mm2) if compared with the rest of sizes at the same volume fraction reaching (7466 N/mm2 for 65 µm, 6666 N/mm2 for 75 µm ). Through the results we note that for the particle size and fiber effect in improving the mechanical behavior of the composite material prepared.